Sociological Implications in Crime Prevention: Narrowing the Gap between Theory and Practice - Havrdova, Eglė (Sociologija. Mintis ir veiksmas, 2004)
The sociological research becomes an important source of information providing knowledge for the social-policy advice, which should terminate the ignorance of social dimensions in crime prevention. This essay, therefore, attempts to examine, what sociological perspectives in criminology offer for the “new science of crime prevention”. It will demonstrate the development of sociological thought in criminology from traditional to modern argumentation emphasizing the significance of theoretical approaches to the rebirth of “the social” in crime prevention.
Keywords: crime; prevention; theory; practice